Faktor Yang Memengaruhi Kepatuhan Minum Obat Pada Pasien Hipertensi Di Puskesmas Paringgonan Kecamatan Ulu Barumun Kabupaten Padang Lawas - Yulika Fitriani; Ismail Efendy; Asriwati Asriwati (STIKES Columbia Asia Medan, 2024)
Data from the World Health Organization (WHO) in 2020 states that developing economies have 40% of people with hypertension while developed countries only 35%, the African region holds the highest position of people with hypertension, which is 40% and Southeast Asia 36%. The purpose of the study was to analyze factors that influence adherence to taking medication in hypertensive patients at the Paringgonan Health Center, Ulu Barumun District, Padang Lawas Regency. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all 95 hypertensive patients, all of whom were sampled using the total population technique. Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression.The results of logistic regression research show that there is an effect of education p = 0.000, knowledge p = 0.000, distance of residence p = 0.000, emotional support p = 0.006 and duration of taking medication p = 0.000. While the dominant factor influencing adherence to taking medication in hypertensive patients is knowledge p = 0.000 with Exp(B) = 68.614.The conclusion of this study is that there is an influence of education, knowledge, distance of residence, emotional support and duration of taking medication. The dominant factor, namely knowledge, influences compliance with taking medication in hypertensive patients at the Paringgonan Health Center, Ulu Barumun District, Padang Lawas Regency. It is recommended that the Puskesmas be taken into consideration and input in improving the implementation of counseling and improving the performance of health workers in carrying out policies and intervening in adherence to taking hypertension medication in collaboration with health workers from Puskesmas Paringgonan and PMO so that the objectives of the program are implemented and are expected to reduce the number of cases of hypertension.